2021
DOI: 10.1016/j.jhazmat.2021.126526
|View full text |Cite
|
Sign up to set email alerts
|

Microbial biofilm composition and polymer degradation of compostable and non-compostable plastics immersed in the marine environment

Abstract: Different plastic types considered as compostable are found on the market such as petro-based (e.g., polybutylene adipate terephthalate (PBAT)) or bio-based plastics (e.g., polylactic acid, (PLA)). Even if their degradation has been confirmed in industrial compost conditions, investigation of their degradation in natural marine environment has been limited. To better understand biodegradation into natural marine environment, commercial compostable (PBAT, semi-crystalline and amorphous PLA) and non-compostable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…However, similarly to previous biofouling experiments performed in the field (Delacuvellerie et al 2021), the changes in surface properties are observed to be not homogeneous across the particle surface in the different samples. This is observable, for example, by the appearance of the sharp peak of glycosidic bond in only half of the samples (Fig.…”
Section: Chemical and Biological Ageing: Comparison Of The Effects On...supporting
confidence: 73%
See 2 more Smart Citations
“…However, similarly to previous biofouling experiments performed in the field (Delacuvellerie et al 2021), the changes in surface properties are observed to be not homogeneous across the particle surface in the different samples. This is observable, for example, by the appearance of the sharp peak of glycosidic bond in only half of the samples (Fig.…”
Section: Chemical and Biological Ageing: Comparison Of The Effects On...supporting
confidence: 73%
“…Our multi-tiered laboratory test confirms this hypothesis, showing that plastic surface physicochemical properties are strongly affected by biofouling. Since the colonization of plastic surfaces by different microorganisms has been reported for litter and microplastics collected in a variety of aquatic systems (Nava and Leoni 2021;Delacuvellerie et al 2021;Deng et al 2021;, this process needs further investigation in future studies, in order to more realistically mimic the environmental behavior of (micro) plastics.…”
Section: Toward a Better Understanding Of Environmental Plastic Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular weight reduction, mainly caused by the chain shortening, is a representative indicator for the hydrolysis of BPs, since only in hydrolysis can there be a measurable and significant molecular weight reduction. Due to this, a greater weight loss ratio than molecular weight reduction indicates that surface erosion predominates, such as that for PCL [50,52] and PHA [47] . A contrary situation indicates that bulk erosion is more important than surface erosion at this stage, as happens to PBS, PBAT [52] , and PLA [50] .…”
Section: Biodegradation Process and Description Indicatorsmentioning
confidence: 99%
“…As plastics are designed to last, plastic waste accumulate in the marine environment for long time (Delacuvellerie et al, 2021;Wang et al, 2016). Durign this period, and under the influence of a number of factors such as UV irradiation, oxidants, hydrolysis and mechanical abrasion, large plastic pieces disintegrate into smaller fragments (< 5 mm) (Song et al, 2017) generally J o u r n a l P r e -p r o o f referred to as MPs.…”
Section: Introductionmentioning
confidence: 99%